2003
DOI: 10.1086/378398
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Observations in a Low Synchrotron Emission Field at 1.4 GHz

Abstract: We present the first observation of the diffuse polarized synchrotron radiation of a patch (∼ 3 • × 3 • ) in the BOOMERanG field, one of the areas with the lowest CMB foreground emission. The work has been carried out with the Australia Telescope Compact Array at 1.4 GHz with 3.4 arcmin resolution and sensitivity of ∼ 0.18 mJy beam −1 . The mean polarized signal has been found to be P rms = (Q 2 rms + U 2 rms ) = 11.6 ± 0.6 mK, nearly one order of magnitude below than in the Galactic Plane. Extrapolations to f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…Patchy high latitude observations at frequencies between 0.408 and 1.411 GHz are collected in Brouw & Spoelstra (1976). New observations carried out with the ATCA telescope at 1.4 GHz (Bernardi et al 2003) and at 2.3 GHz (Carretti et al 2005) in the same high galactic latitude region observed by our experiment show that the polarized synchrotron emission is very weak. A naive extrapolation to 145 GHz predicts a polarization of 0.2 µK rms, small with respect to the √ EE ∼ 4 µK expected in the concordance model.…”
Section: Introductionsupporting
confidence: 74%
“…Patchy high latitude observations at frequencies between 0.408 and 1.411 GHz are collected in Brouw & Spoelstra (1976). New observations carried out with the ATCA telescope at 1.4 GHz (Bernardi et al 2003) and at 2.3 GHz (Carretti et al 2005) in the same high galactic latitude region observed by our experiment show that the polarized synchrotron emission is very weak. A naive extrapolation to 145 GHz predicts a polarization of 0.2 µK rms, small with respect to the √ EE ∼ 4 µK expected in the concordance model.…”
Section: Introductionsupporting
confidence: 74%
“…The other symbols show errors in relative calibration (stars), bolometer time constant (upward-pointing triangles) and polarization angle (downward-pointing triangles). Because errors in absolute calibration and polarization efficiency are multiplicative factors that act identically on each bin, their effect is left off this plot and reported instead in Table 6 1.4 GHz (Bernardi et al 2003) and 2.3 GHz (Carretti et al 2006). A naive extrapolation of these synchrotron results to 145 GHz predicts a signal of 0.2 K rms compared to a $3 K rms expected from the fiducial ÃCDM model given our beam.…”
Section: Foregroundsmentioning
confidence: 91%
“…The diffuse synchrotron emission of the Galaxy is considered to be one of the most relevant polarization contaminant and is expected to dominate the foreground contribution at frequencies less than 100 GHz. Recent measurements performed in a low‐emission area at both 1.4 and 2.3 GHz indicate that the synchrotron signal does not represent an obstacle for the E mode at high Galactic latitude and at frequencies higher than 30 GHz (Bernardi et al 2003; Carretti et al 2005a,b). However, this is just one sample that may not be representative of the situation throughout high Galactic latitudes, and other measurements in different areas are required to confirm this first evaluation.…”
Section: Introductionmentioning
confidence: 99%